Speech Brought with Children Who Are Not Fully Developed Logopedic in The Sliding Correction Work System the Importance of Rhythmics (Open Academia: Journal of Scholarly Research, 2024)
in the process of Speech Communication, people exchange ideas and influence one another. Speech communication is carried out through language, language is a system of phonetic, lexical and grammatical means. This article summarizes the speech clinical manifestations of a defect in underdeveloped children, depending on the type of defect the importance of logorhythmic actions in correctional work processes is highlighted.